An extension of the improving and embedding project management practice framework: Case study analysis. Issue 4 (2nd December 2019) - Fernandes, Gabriela; Araújo, Madalena; Pinto, Eduardo B.; Machado, Ricardo J.
Abstract : Purpose: The purpose of this paper is to develop and test an extension of a previously conceived framework for improving and embedding project management (PM) practice in organisations. The framework identifies the most useful project management improvement initiatives (PMIIs) and the key factors for embedding PM practice. However, professionals need guidance on how to operationalise such framework in their organisations, therefore a method for applying the framework is developed. Design/methodology/approach: The method being proposed for applying the framework is demonstrated and tested with a large University–Industry consortium case study. During the case study analysis three research methods were applied: participant observation, document analysis and focus groups. Findings: In what concerns both the PMIIs and key embedding factors in the framework, the proposed method comprises their acknowledgement, scoring, relevance analysis, selection and planning. The detailed report on how the framework was applied in the particular case study also sheds light on how University–Industry consortiums can make use of PM to become more successful. Research limitations/implications: The research was performed using only one case study which limits the generalisability of its findings. Practical implications: Detailed guidance is provided for applying the framework's both constructs, "improving" and "embedding", through a set of clear steps. Originality/value: The paper shows the explanatory power of the framework for improving and embedding PM practice in a case study, demonstrating that the method for its application is practical and suitable.